Prevalence of protective antibody levels against hepatitis B infection among healthcare workers in a tertiary care hospital in India - Ramesh Thanikachalam; Sathyan Elangovan; Jercy Grace (Asian Journal of Medical Sciences, 2023)
Background: Hepatitis B virus (HBV) infection affects more than 2 billion individuals globally HBV. The chance of dying from liver cirrhosis, acute fulminant liver disease, or hepatocellular carcinoma (HCC) is present in 240 million of these chronic HBV carriers (HCC).